NHC-catalyzed ester activation : access to sterically congested spirocyclic oxindoles via reaction of α-aryl esters and unsaturated imines - Hao, Lin (2014)
Carboxylic esters can be readily obtained at low cost. Therefore, asymmetric catalytic activation of esters should provide useful strategies for organic synthesis. Here we report a N-heterocyclic carbene (NHC)-mediated reaction of α-aryl acetic esters with oxindole-derived α,β-unsaturated imines. The reaction involves the formation of NHC-bound ester enolate intermediate from an ester as a key step, and furnishes spirocyclic oxindole products. The sterically congested spirocyclic oxindole bears a newly formed six-membered δ-lactams and cannot be easily prepared using other methods.